ESSÉR JEMMU’: An Ecological Adaptation Ritual in a House Construction in Madura - Emna Laisa; Indah Husnul Khotimah (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2021)
For the people of Bungbungan, it is imperative that they build a new house, especially when they have a daughter. This is based on the concept of tanéyan lanjhâng which adheres to auxorilocality and matrilocality. The purpose of this study is to describe the essence of a house for the Bungbungan community, various important guidelines in the preparation of building a new house, various ritual offerings, and ritual practice of essér jemmu’. This study is an ethnographic study based on Pierre Bourdieu’s habitus theory to describe the pattern of relations between Islam in the context of pesantren and of the villagers in addressing the ritual of essér jemmu’ as an ecological adaptation ritual in a house construction. The result of this study shows that the house could be a symbol of social status as well as a sign that girls should not be brought to their husband’s house. The process of building a new house begins with various rituals influenced by myths including to determine the direction and layout of the house which are based on the pancabara and babukon. Various offerings are put into a polo’ then planted in the yard. The practice of essér jemmu’ ritual consists of prayers and ritual practices led by a kiai from pesantren or from the village, in which it shows a pattern of domination-subordination relationship of Islam of the pesantren to village Islam. [Bagi masyarakat Bungbungan, membangun rumah baru merupakan sebuah keharusan, terutama jika memiliki anak perempuan. Hal ini berdasarkan konsep tanéyan lanjhâng yang menganut uksorilokalitas dan matrilokalitas. Tujuan penelitian ini adalah untuk mendeskripsikan hakikat rumah bagi masyarakat Bungbungan, berbagai pedoman penting dalam persiapan pembuatan rumah, ragam sesaji ritual, dan praktik ritual essér jemmu’. Penelitian ini merupakan penelitian etnografi yang berdasarkan teori habitus Pierre Bourdieu untuk mendeskripsikan pola relasi antara Islam pesantren dan Islam kampung dalam menyikapi praktik ritual essér jemmu’ sebagai ritual adaptasi ekologis dalam pembangunan rumah. Hasil penelitian menunjukkan bahwa rumah merupakan penanda status sosial sekaligus isyarat bahwa anak perempuan tidak boleh diboyong ke rumah suami. Proses pembangunan rumah diawali dengan berbagai ritual yang dipengaruhi oleh mitos yang meliputi penentuan arah dan tata letak rumah berdasarkan pancabara dan babukon. Ragam sesaji dimasukkan ke dalam polo’ kemudian ditanam di pekarangan. Praktik ritual essér jemmu’ berisi doa-doa dan laku ritual yang dipimpin kiai pesantren atau kiai kampung yang menunjukkan pola relasi dominasi-subordinasi Islam pesantren terhadap Islam kampung]